HUBUNGAN ANTARA KUALITAS TIDUR DAN DAYA KONSENTRASI MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - I Made Ari Sastrawan; I Putu Adiartha Griadhi (Universitas Udayana, 2017)
Today appeared various changes in behavior patterns and lifestyle of the people, especially in teenagers and young adults that can affect the quality of sleep. Quality of sleep is considered to have important roles to physical and mental condition, including concentration. This study was aimed to determine the condition of the quality of sleep and concentration in the first semester students of Medical Education Program Faculty of Medicine, University of Udayana Academic Year 2014-2015, as well as correlation between quality of sleep and concentration. The study design was cross-sectional analytic study, the number of samples is 100 students first semester requested to fill out a questionnaire Pittsburgh Sleep Quality Index for measure quality of sleep, and the Continuous Performance Task measurement for measure the power of concentration. The results of this study displayed through tables and the research hypothesis analysed by Chi-Square test. The results showed, 23 people (23%) had a good sleep quality and 77 people (77%) had poor sleep quality. For the concentration, 34 people (34%) had good concentration, and 66 people (66%) had poor concentration. Chi-Square analysis results, there is correlation between sleep quality and concentration with p value <0.05. It can be concluded that the condition sleep quality and concentration power of first semester students of Medical Education Program Faculty of Medicine, University of Udayana Academic Year 2014-2015 was dominated by poor sleep quality and poor concentration. There was significant correlation between quality of sleep and concentration. Keywords: Quality of Sleep, Concentration, Correlation